-4 5/9 + (-1 2/3)[tex] - 4 \frac{5}{9} + ( - 1 \frac{2}{3} )[/tex]
![4 59 1 23tex 4 frac59 1 frac23 tex class=](https://us-static.z-dn.net/files/d0c/7600e0c15d96ec85ac98d7ea93544b19.png)
Answer:
-6 2/9
Explanation:
Given the expression:
[tex]-4\frac{5}{9}+(-1\frac{2}{3})[/tex]First, open the brackets:
[tex]=-4\frac{5}{9}-1\frac{2}{3}[/tex]Next, change the fractions to improper fractions:
[tex]=-\frac{41}{9}-\frac{5}{3}[/tex]Then, take the lowest common multiple of 9 and 3 to combine the fractions:
[tex]\begin{gathered} =\frac{-41-5(3)}{9} \\ =\frac{-41-15}{9} \\ =\frac{-56}{9} \\ =-6\frac{2}{9} \end{gathered}[/tex]The result is -6 2/9.